(untitled) (Altre Modernità, 2014)
It is only appropriate to begin with his face. The intense, rainbow-colored Mandela portrait that opens this issue is the work of a young Indonesian digital artist, Ihsanulhakim, who captures a serious, reflective and aged version of the South African leader. The writing on the top left of the image is a quote from Mandela’s famous reflection on death translated into Indonesian: “Death is something inevitable. When a man has done what he considers to be his duty to his people and his country, he can rest in peace”.[1] [1] RIP Nelson Mandela © Muhammad Ihsanulhakim. I wish to thank the artist for generously allowing Altre Modernità to reproduce his work. The quote is from an interview for the documentary “Mandela”, 1994, in Nelson Mandela by Himself: The Authorised Book of Quotations © 2010 by Nelson R. Mandela and The Nelson Mandela Foundation).